Perceived Stress and Associated Factors in Russian Medical and Dental Students: A Cross-Sectional Study in North-West Russia - Sergei N. Drachev; Lina Stangvaltaite-Mouhat; Napat Limchaichana Bolstad; Jan-Are K. Johnsen; Tatiana N. Yushmanova; Tordis A. Trovik (International Journal of Environmental Research and Public Health, 2020)
The aim was to assess perceived stress (PS) and factors associated with PS in Russian medical and dental students. A total of 406 medical and 283 dental students aged 18–25 years that attended the Northern State Medical University in Arkhangelsk, North-West Russia participated in this cross-sectional study. A structured, self-administered questionnaire was used to collect information on socio-demographic and socioeconomic factors, oral health (OH) behavior, and self-reported OH. All students were clinically examined to assess dental caries, oral hygiene, and gingiva. PS was measured by the Perceived Stress Scale 10 (PSS-10). Of the students, 26.0%, 69.1%, and 4.9% reported low, moderate, and high PS, respectively. Female sex (b = 2.28, 95% confidence interval (CI): 1.38–3.18), dental faculty (b = 1.74, 95% CI: 0.94–2.54), low subjective socioeconomic status (SES) (b = 1.71, 95% CI: 0.91–2.51), and irregular dental visits (b = 1.65, 95% CI: 0.72–2.58) were associated with higher PSS-10 score. These factors were assumed to be clinical meaningful, given that minimal clinically important difference of PSS-10 fell between 2.19 and 2.66 points. The majority of the medical and dental students reported moderate PS. Based on statistical significance and clinical meaningfulness, socio-demographic factors (sex, faculty), subjective SES, and OH behavior (regularity of dental visits) were associated with PS.